Heterogeneity of Interactive Learning Media Outcomes for Improving Mathematical Competence: A Systematic Literature Review - Teapon, Nurhuda; Kusumah, Yaya Sukjaya; Pakaya, Yusril Mahendra; Adjis, Vidia Amalia; Sartika, Rahma Adinda (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This study analyzes how using interactive learning media affects math skills in different educational levels: elementary school, middle school, high school, and college. We used the Systematic Literature Review method, looking at 90 studies published between 2014 and 2023. These studies focused on how interactive learning media influences math understanding, problem-solving, communication, representation, and connections. We included all relevant school levels in our research. Our main questions were about how interactive learning media impacts students' math skills, considering factors like the school year, education level, and the number of students. The results of our analysis show a significant increase in research on this topic over the past ten years. Specifically, more studies focused on high school and college students, and larger groups of 30 or more students were common in these studies.